IMPLEMENTATION OF PROBLEM BASED LEARNING IN DYNAMIC FLUID LESSON TO INCREASE PROBLEM SOLVING SKILL STUDENT’S CLAS XI ON SMAN 1 JEMBER - ANINDITO KARTIKA PUTRI, ELFANDARI (Inovasi Pendidikan Fisika, 2018)
This research aimed to describe the students problem solving skills on dynamic fluid topic after applied problem based learning model. The pre experimental research adopted one group pre-test post-test design applied to 106 student at 11th grade in SMAN 1 Jember. This research use three class (XI MIA 1, XI MIA 2, and XI MIA 3) totaling 106 students. Before applying the problem based learning model, student were given a pre-test to measure the initial condition of the students, Pre-test given in the form of problem-solving problems. Then apply the problem learning model on the dynamic fluid material. After applying the learning model, the student was given a post-test in the form of problem solving problem. The data obtained were analyzed using paired t-test, n-gain, and ANAVA. The results showed that learning was done with good category. Problem solving skills in all three classes experienced consistent and significant improvement at α = 5% and n-gain for each category indicator. Positive response is shown by all students in all three classes to the learning model based on the problem that has been implemented.   Keywords: Problem Based learning, students Problem solving skill, Fluid Dynamic, Senior High school students